2019
DOI: 10.1371/journal.pone.0217882
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-like features and spatial memory problems as a consequence of hippocampal SV2A expression

Abstract: The Synaptic Vesicle Protein 2A (SV2A) is a transmembrane protein whose presence is reduced both in animal models and in patients with chronic epilepsy. Besides its implication in the epileptic process, the behavioural consequences of the changes in its expression remain unclear. The purpose of our research is to better understand the possible role(s) of this protein through the phenotype of cKO ( Grik4 Cre+/- , SV2A lox/lox ) mice, male and female, which present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Recent work by Serrano et al showed that heterozygous SV2A knockout animals demonstrate altered habituation to novel environments, increased anxiety levels, and spatial memory deficits. No changes were observed in fear conditioning or locomotor behavior …”
Section: Sv2s In Neurological Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…Recent work by Serrano et al showed that heterozygous SV2A knockout animals demonstrate altered habituation to novel environments, increased anxiety levels, and spatial memory deficits. No changes were observed in fear conditioning or locomotor behavior …”
Section: Sv2s In Neurological Diseasementioning
confidence: 93%
“…No changes were observed in fear conditioning or locomotor behavior. 154 SV2s in Peripheral Nervous and Neuroendocrine Disorders. SV2 paralogues have been implicated in spinal muscular atrophy (SMA), the leading genetic cause of infant mortality.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…Mice that lack SV2A develop severe seizures and die within 3 weeks of birth 58 , whereas mice heterozygous for one functional copy of Sv2a have a normal lifespan, but develop an anxiety-like phenotype 50 . Conditional knockout mice with decreased SV2A in hippocampus are free of epileptic seizures but show elevated levels of anxiety, as measured with the Elevated Plus Maze 59 . Genetically epilepsy-prone rats exhibit an anxiety phenotype across multiple measures prior to having developed epileptic seizures 60 .…”
Section: Discussionmentioning
confidence: 99%
“…If Richelle was, at least in part, an accidental psychopharmacologist, he was certainly an active one, producing more than twenty articles on the subject, and work on psychopharmacology and behavioural neuroscience continues to this day in the laboratory he founded (e.g., Didone, van Ingelgom, Tirelli, & Quartemont, 2019 ; Serrano et al, 2019 ). However, as well as pharmacological work, in his early years Richelle also conducted some purely behavioural studies, and I will mention two of the more unusual ones.…”
Section: The Early Years: Mostly Psychopharmacologymentioning
confidence: 99%